Pulse oximetry as a dental pulp test: A scoping review to identify barriers hindering the use of oximeters in clinical practice - Rafaela Hartmann Kasper; Mabiéli Rabelo Coelho; Sergio Augusto Quevedo Miguens-Jr; Renata Grazziotin-Soares; Fernando Branco Barletta (Elsevier, 2024)
Background and Objective: Although medical pulse oximeters are considered effective for endodontic diagnoses, the method remains uncommon in current dental practice. The aim of the present scoping review was to investigate clinical factors that exert a negative impact on the use of pulse oximeters in dental practice. Methods: This study followed the PRISMA-ScR guidelines and the protocol was prospectively registered in the Open Science Framework (https://doi.org/10.17605/OSF.IO/3GQCE). A comprehensive search of the MEDLINE (via PubMed), Cochrane Library, and Web of Science databases was performed in December 2022 for articles published in English or Spanish. All types of clinical studies were included, except comments, letters to the editor, and abstracts. Two independent investigators analyzed 45 full-text articles. Data extraction included general characteristics, oxygen saturation levels, and limiting factors/barriers to the use of oximeters as pulp testers. Results: The search of the databases yielded 1,300 records and 38 were included (quantitative data extraction was performed for 35 and three articles were systematic reviews). Publications were highest in number between 2016 and 2017, with an evident reduction occurring after 2021. The oxygen saturation level for sound/vital maxillary anterior teeth was 84.99% (overall mean). The main limiting factors/barriers were i) the difficulty in maintaining the two light-emitting diodes parallel during pulp tests, ii) infrared light diffraction by enamel/dentin/gingiva, and iii) the diversity of patient ages in studies. Conclusion: This scoping review encountered noteworthy findings associated with the impracticability of using medical pulse oximeters as dental pulp testers. The recent decrease in the frequency of published studies compared to approximately seven years ago may imply a negative trend in the use of the method.